2007
DOI: 10.1104/pp.107.101600
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Gene Expression Profiling Reveals Conserved and Novel Molecular Functions of the Stigma in Rice

Abstract: In angiosperms, the stigma provides initial nutrients and guidance cues for pollen grain germination and tube growth. However, little is known about the genes that regulate these processes in rice (Oryza sativa). Here, we generate rice stigmaspecific or -preferential gene expression profiles through comparing genome-wide expression patterns of hand-dissected, unpollinated stigma at anthesis with seven tissues, including seedling shoot, seedling root, mature anther, ovary at anthesis, seeds 5 d after pollinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
109
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(119 citation statements)
references
References 83 publications
9
109
0
1
Order By: Relevance
“…The "Intracellular trafficking, secretion, and vesicular transport" (2.8%), "Carbohydrate transport and metabolism" (2.6%), and "Lipid transport and metabolism" (2.3%) categories contain the gene functions important for the roles exerted by the stigmatic secretory zone and the stylar transmitting tissue in secreting the exudate, which is rich in carbohydrates and lipids (Cresti et al, 1986). The "Defense mechanisms" (2.3%) category is also well represented, consistent with what was observed for the Arabidopsis stigma and transmitting tract gene sets (Tung et al, 2005) and for the rice stigma gene set (Li et al, 2007). Our data corroborate the notion of an overlap of genetic programs regulating reproduction processes and stress/defense responses, as proposed by Li et al (2007).…”
supporting
confidence: 66%
See 1 more Smart Citation
“…The "Intracellular trafficking, secretion, and vesicular transport" (2.8%), "Carbohydrate transport and metabolism" (2.6%), and "Lipid transport and metabolism" (2.3%) categories contain the gene functions important for the roles exerted by the stigmatic secretory zone and the stylar transmitting tissue in secreting the exudate, which is rich in carbohydrates and lipids (Cresti et al, 1986). The "Defense mechanisms" (2.3%) category is also well represented, consistent with what was observed for the Arabidopsis stigma and transmitting tract gene sets (Tung et al, 2005) and for the rice stigma gene set (Li et al, 2007). Our data corroborate the notion of an overlap of genetic programs regulating reproduction processes and stress/defense responses, as proposed by Li et al (2007).…”
supporting
confidence: 66%
“…It is expected that many of these genes are stigma/style specific or preferential. Recent large-scale studies have identified stigma/style-specific genes in the dry stigma species Arabidopsis and rice (Swanson et al, 2005;Tung et al, 2005;Li et al, 2007). However, in wet stigma species, only a few individual genes have been characterized so far, and little is known about the stigma/style-specific genes important for successful pollination and reproduction.…”
mentioning
confidence: 99%
“…This normalization allowed cross-comparison of arrays from all of the different studies at once. The arrays analyzed included all of the arrays from this study, together with publicly available rice genome arrays carried out from different tissues/ conditions, including 7-d-old seedlings that were untreated, drought stressed, salt stressed, or cold stressed (GSE6901; Jain et al, 2007); seeds collected at 5 d following pollination, 10-d-old embryos, 10-d-old endosperms, seedling roots, seedling shoots, unpollinated stigmas (at antithesis), ovaries (at antithesis), mature anthers, and suspension cells (GSE7951; Li et al, 2007); aerobically grown coleoptiles (4 d) and anoxically grown coleoptiles (4 d; GSE6908; Lasanthi- Kudahettige et al, 2007); crowns and growing points under salt stress and control conditions in sensitive and tolerant mutants in subspecies indica and japonica (GSE4438; Walia et al, 2007); crowns and growing points under control and salt stress conditions in subspecies indica and japonica (GDS1383; Walia et al, 2005); and leaves following biotic stress and control treatments (GSE7256; Ribot et al, 2008).…”
Section: Public Rice Microarray Data Analysis and Comparisonmentioning
confidence: 99%
“…We obtained 203 and 322 Affymetrix CEL files for rice (Oryza sativa) and Arabidopsis (Arabidopsis thaliana), respectively, from the National Center for Biotechnology Information Gene Expression Omnibus database monitoring the transcriptional activity in different tissues and developmental stages (Schmid et al, 2005;Jain et al, 2007;Li et al, 2007), root cell types (Birnbaum et al, 2003;Norton et al, 2008), and under different stress conditions (Walia et al, 2005;Kilian et al, 2007;Swarbrick et al, 2008). The ATH1 microarray slides were processed with a custom-made CDF measuring 19,937 genes as described before .…”
Section: Expression Datamentioning
confidence: 99%